2017
DOI: 10.15233/gfz.2017.34.6
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic susceptibility and natural gamma radioactivity as indirect proxies for characterization of sandstones and limestones of the Sabinas basin

Abstract: An analysis of magnetic susceptibility and natural gamma radioactivity is presented as indirect proxies of the characteristics of sandstones and limestones of the Sabinas basin. These rocks are located in the sedimentary sequence ranging from the Upper Jurassic to the Cretaceous. The magnetic susceptibility indicates changes in the magnetic composition of these rocks and suggests changes in their weathering degree. Ranges of values of magnetic susceptibility in sandstones and limestones allow classifying them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Specifically, the limestones of transect 2 have higher MS than those of transect 1 (Figure 10), showing the greater intensity of the metasomatic process in the rocks of transect 2 and, therefore, greater enrichment in paramagnetic (e.g., epigenetic sulfides) and ferromagnetic minerals coming from the intrusion. Generally, it is observed that the host rocks close to the plutons have higher MS values than the same facies remote from the influence of these plutons (Batista-Rodríguez et al, 2017). This corroborates the observed effect of emplacement of the plutons on the magnetic composition of host rocks.…”
Section: Characteristics and Alteration Of The Host Sedimentary Rockssupporting
confidence: 83%
See 1 more Smart Citation
“…Specifically, the limestones of transect 2 have higher MS than those of transect 1 (Figure 10), showing the greater intensity of the metasomatic process in the rocks of transect 2 and, therefore, greater enrichment in paramagnetic (e.g., epigenetic sulfides) and ferromagnetic minerals coming from the intrusion. Generally, it is observed that the host rocks close to the plutons have higher MS values than the same facies remote from the influence of these plutons (Batista-Rodríguez et al, 2017). This corroborates the observed effect of emplacement of the plutons on the magnetic composition of host rocks.…”
Section: Characteristics and Alteration Of The Host Sedimentary Rockssupporting
confidence: 83%
“…with a cubic habitus, are observed (Figure 5b), showing the epigenetic origin of this mineral. It is possible that this mineral has been incorporated into the sedimentary rock through hydrothermal processes during the emplacement of the pluton (Batista-Rodríguez et al, 2017).…”
Section: Characteristics and Alteration Of The Host Sedimentary Rocksmentioning
confidence: 99%
“…have the highest contents of paramagnetic minerals or at least medium to low ferromagnetic mineral content [9]. Considering the typical composition of sedimentary rocks [14] and the results of petrographic analyzes in this research ( Figure 5 and Figure 6) and previous ones [25], these minerals could be mainly iron oxides and hydroxides (e.g. magnetite, ilmenite, hematite and goethite) and iron sulphides (e.g.…”
Section: κ and Ngr As Indirect Indicators Of Impurities In Cretaceousmentioning
confidence: 67%
“…In this case, the high values of κ and the high concentrations of U probably linked to the iron sulfides and organic matter, respectively. Previous studies report both components in these rocks [25]. It is likely that these minerals were acquired during the accumulation of organic matter.…”
Section: κ and Ngr As Indirect Indicators Of Impurities In Cretaceousmentioning
confidence: 74%
See 1 more Smart Citation